Interfacial passivation of n-ZnO/p-Si heterojunction by CuI thin layer *Project supported by the "333 High-Level Talents Training Project" in Jiangsu Province of China (No. BRA2016111), the Qing Lan Project of Jiangsu Higher Education, the Science and Technology Program of Changzhou (No. CE20175031), the Jiangsu Province Key R & D Projects (No. BE2016200), and the High-Tech Key Laboratory of Changzhou (No. CM20173003). (December 2018) - Xiong, Chao; Xiao, Jin; Chen, Lei; Du, Wenhan; Xu, Weilong; Hou, Dongdong
Abstract: The ZnO/Si heterojunction diode can be integrated with the Si process, which has attracted great attention in recent years. However, the large number of interface states at the ZnO/ Si heterojunction interface could adversely affect its optoelectronic properties. Here, n-type ZnO thin film was deposited on p-Si substrate for formation of an n-ZnO/p-Si heterojunction substrate. To passivate the ZnO/Si interface, a thin CuI film interface passivation layer was inserted at the ZnO/p-Si heterojunction interface. Electrical characterization such as I–V and C–V characteristic curves confirmed the significant improvement of the heterojunction properties e.g. enhancement of forward current injection, reduction of reverse current and improvement of the rectification ratio. These results showed that the passivation of interface is critical for ZnO/Si heterojunctions.